Homelessness and housing assistance among persons with HIV, and associations with HIV care and viral suppression, New York City 2018. - Ellen Weiss Wiewel; Yaoyu Zhong; Qiang Xia; Christopher M Beattie; Paul A Brown; Pam X Farquhar; John F Rojas (PLoS ONE, 2023)
Objectives To measure housing assistance and homelessness among persons living with HIV (PLWH) and their association with health. Methods Exposure categories were: experiencing homelessness (per emergency shelter use or self-report), receiving housing assistance (per housing subsidy) without homelessness, or neither homelessness nor receiving housing assistance. Outcomes were: engagement (≥1 visit) and retention (≥2 visits ≥90 days apart) in HIV-related medical care and one-time (latest viral load) and durable (≥1 viral load test, all suppressed) HIV viral suppression (<200 copies/mL). Among PLWH in New York City (NYC), we calculated and conducted modified Poisson regressions of the four outcomes according to exposure category. Results During 2018, 45% of NYC's 84,053 PLWH received housing assistance, and 8% experienced homelessness. Relative to homelessness, receipt of assistance without homelessness was associated with 3-7% higher adjusted relative risk (ARR) of engagement and retention in care and 31-64% higher ARR of one-time and durable viral suppression. Relative to not receiving assistance, receipt of assistance without homelessness was associated with 6-18% higher ARR of care and 2-5% lower ARR of viral suppression. Conclusions Programs promoting housing stability may support HIV care and viral suppression, particularly if preventing homelessness. These may help improve HIV care and suppression rates.